Acoustic Property Reconstruction of a Neonate Yangtze Finless Porpoise's (Neophocaena asiaeorientalis) Head Based on CT Imaging - Wei, Chong; Wang, Zhitao; Song, Zhongchang; Wang, Kexiong; Wang, Ding; Au, Whitlow WL; Zhang, Yu (PUBLIC LIBRARY SCIENCE, 2015)
The reconstruction of the acoustic properties of a neonate finless porpoise's head was performed using X-ray computed tomography (CT). The head of the deceased neonate porpoise was also segmented across the body axis and cut into slices. The averaged sound velocity and density were measured, and the Hounsfield units (HU) of the corresponding slices were obtained from computed tomography scanning. A regression analysis was employed to show the linear relationships between the Hounsfield unit and both sound velocity and density of samples. Furthermore, the CT imaging data were used to compare the HU value, sound velocity, density and acoustic characteristic impedance of the main tissues in the porpoise's head. The results showed that the linear relationships between HU and both sound velocity and density were qualitatively consistent with previous studies on Indo-pacific humpback dolphins and Cuvier's beaked whales. However, there was no significant increase of the sound velocity and acoustic impedance from the inner core to the outer layer in this neonate finless porpoise's melon.